INTERAKSI HUKUM ADAT DAN SISTEM HUKUM NASIONAL DI ERA MODERN: STUDI KEPUSTAKAAN TERHADAP EKSISTENSI DAN RELEVANSI HUKUM ADAT BADUY PASCA REFORMASI - Gunawan Widjaja; Wagiman (INTELIGENSIA MEDIA, 2025)
This study discusses the interaction between Baduy customary law and the national legal system in the post-Reform era, using a literature review approach. Baduy customary law has maintained its existence as a legal system amid modernisation and changes in national regulations. This study highlights the internal mechanisms, community leadership, and commitment of the Baduy people in preserving their ancestral norms. On the other hand, formal recognition through the constitution and national laws provides legal legitimacy to Baduy customary law; however, its implementation still faces challenges such as overlapping regulations and potential normative conflicts. This study emphasizes the importance of dialogue, negotiation, and harmonisation between customary communities and the state to ensure that customary law can coexist and synergise with the national legal system without sacrificing cultural values. This study concludes that Baduy customary law can serve as an inclusive model for the development of national legal policies that respect local wisdom as a source of legal and cultural strength for the nation.